PENGARUH EKSTRAKURIKULER ROHIS PADA MASA PANDEMI COVID-19 TERHADAP PEMBENTUKAN KARAKTER PEDULI SOSIAL DI SMK NEGERI 1 PEKANBARU - Putri, Nabilla Ananda; Hambali, Hambali; Eddison, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research was motivated by Rohis extracurricular activities thatcontinue to carry out activities during the Covid-19 pandemic and the social carecharacter possessed by students at SMK Negeri 1 Pekanbaru. The formulation of theproblem in this study is whether there is an effect of Rohis extracurricular during theCovid-19 pandemic on the establishment of social care characters at SMK Negeri 1Pekanbaru. The purpose of this study was to determine whether there was an effect ofRohis extracurricular during the Covid-19 pandemic on the establishment of social carecharacters at SMK Negeri 1 Pekanbaru. The theoretical benefits of research are toincrease knowledge, insight and understanding for schools regarding the influence ofRohis extracurriculars during the Covid-19 pandemic on the establishment of socialcare characters at SMK Negeri 1 Pekanbaru. The practical benefits of research are as areference for further research. The research population was 62 students who took partin Rohis extracurricular at SMK Negeri 1 Pekanbaru. Determination of the sample inthe study using a total sampling technique. Data collection methods are observation,interviews, questionnaires, and documentation. Processing of data with quantitativedescriptive statistical analysis using a simple linear regression formula assisted by theSPSS version 25 application. The hypothesis in this study is accepted, where there is aneffect Rohis extracurriculars during the Covid-19 pandemic on the establishment ofsocial care characters at SMK Negeri 1 Pekanbaru. This is based on the calculation ofthe coefficient of determination (R Square) of 0.305 which implies that the effect of theindependent variable (extracurricular Rohis) on the dependent variable (social carecharacter) is 30.5%, with moderate interpretation results.Key Words: effect, extracurricular, rohis, caring, social.